Persistent low-level viraemia in antiretroviral treatment-experienced patients is not linked to viral resistance or inadequate drug concentrations. (9th July 2020) - Palich, R; Wirden, M; Peytavin, G; Lê, M -P; Seang, S; Abdi, B; Schneider, L; Tubiana, R; Valantin, M -A; Paccoud, O; Soulié, C; Calvez, V; et al.
Abstract: Objectives: To assess genotypic sensitivity scores (GSSs), plasma antiretroviral concentrations (PACs) and immunovirological outcomes at Week 96 (W96) in patients with persistent low-level viraemia (LLV). Methods: On 1 January 2017, we analysed data from patients on three-drug regimens with persistent LLV defined as at least two consecutive plasma viral loads (pVLs) between 21 and 200 copies/mL (including one pVL of ≥50 copies/mL), at the Pitié-Salpêtrière Hospital. Outcomes were: GSS, PACs and HIV-DNA load at study entry; and virological status and proportion of patients with resistance-associated mutations (RAMs) at W96. Results: Fifty-seven patients were included, with median age of 52.6 years (IQR 45.2–57.9), last CD4 count of 658 cells/mm 3 (IQR 462–909) and total ART duration of 10.2 years (IQR 5.7–15.2). LLV duration was 14.0 months (IQR 5.5–22.3). GSS was 3 in 46/57 (81%) patients and PACs were adequate in 53/57 (93%) patients. Median total HIV-DNA was 2.65 log10  copies/10 6  cells (IQR 2.44–2.86). During follow-up, 26/57 (46%) had experienced ART modifications. At W96, 38/57 (67%) patients remained with LLV, 15/60 (26%) had achieved confirmed pVL of <20 copies/mL and 4/57 (7%) had virological failure. The four virological failures were due to three ART interruptions and one incomplete adherence (selection of Y181C RAM). No factors (patient characteristics at study entry, GSS, PACs, total HIV-DNA load and ART modification) were associated with W96 viral outcome, except for time from HIV diagnosis and the LLV duration at study entry. Conclusions: A substantial number of patients harbouring LLV had no resistance to ART and adequate PACs. Two-thirds of these patients remained with this LLV status.